ANALISIS EFEKTIVITAS PELATIHAN TENAGA PENJUALAN DI PERUSAHAAN PERSEWAAN ALAT BERAT PT. SUMBER NUSANTARA ADITYA PRATAMA SURABAYA - Rozaq, Khoirur (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2019)
Investment in HR training is the best practice in the industry that was developed in the information age. Employee competencies and skills are needed by organizations to increase profits. Employees in the marketing division, in this case are sales force. Companies providing assistance for sales training by providing useful training will return results to the company. The purpose of this study was to analyze the training plan for salespeople at PT X Surabaya engaged in heavy equipment rental. This company chooses because of its unique nature if you choose another service company. Qualitative research methods were chosen for this study, data collection was done by interview and observation. The results of this study show how training practices conducted by companies for their sales force are very effective, seen from reactions, learning, behavior, and results for organizations.Keywords: Effectiveness, Sales Force Training, performance, evaluation Training